"It's a coffee with a purpose": perspectives on thinking and working politically in the Pacific. Issue 3 (3rd April 2022) - Wild, Kayli; Kelly, Linda; Roche, Chris
ABSTRACT: Thinking and working politically is an approach to manoeuvring within social and political realities to achieve development goals, which some see as a new orthodoxy [Teskey 2017. Thinking and Working Politically: Are We Seeing the Emergence of a Second Orthodoxy? Governance Working Paper Series, Issue 1. Massachusetts: Abt Associates]. This research explores the practice of thinking and working politically in the Pacific, through in-depth interviews and observation with nine Pacific Islander staff working within a bilateral aid programme in Samoa, Tonga, Vanuatu, and Solomon Islands. The findings provide a rich description of what thinking and working politically entails in small, highly connected island communities, with insights into how these processes can be supported in official aid programmes. Highlights This research unpacks thinking and working politically from the unique perspective of Pacific staff working in a bilateral aid programme. Thinking politically involves knowing the context, who to work with, and when to act. Working politically entails good communication, intuition, flexibility, influence, connecting people, and "playing different cards" at appropriate moments. Building and maintaining relationships is the cornerstone of thinking and working politically but is not always valued by within aid programmes. Moving away from political analysis as donor-led, intelligence-gathering exercises towards investment in locally led processes necessitates genuinely valuing relational work.